PENGARUH SKARIFIKASI PEMOTONGAN DAN KONSENTRASI ASAM SULFAT TERHADAP PERKECAMBAHAN DAN PERTUMBUHAN BIBIT KURMA AJWA (Phoenix dactylifera L.) - Mislenawati; Mardaleni (UIR Press, 2025)
This research aims to determine the effect of cutting scarification and sulfuric acid on the germination of Ajwa date seeds, using a Factorial Completely Randomized Design consisting of two factors. The first factor is cutting scarification, with five levels: without cutting, cutting in the plumule area, cutting in the radicle area, cutting in the plumule and radicle area, and cutting in the embryo area. The second factor is sulfuric acid, with four levels: 0 ml/L, 40 ml/L, 80 ml/L, and 120 ml/L. The parameters observed were germination power, germination time, vigor index, number of leaves, longest leaf length, seedling height, longest root length, fresh weight of seedlings, and dry weight of seedlings. The observation data were analyzed statistically and followed by the Honestly Significant Difference (HSD) test at the 5% level. The results showed that the interaction between cutting scarification and sulfuric acid significantly affected germination rate, longest leaf length, seedling height, longest root length, and the fresh and dry weight of seedlings, but did not significantly affect germination time, vigor index, or number of leaves. The best treatment was cutting scarification in the embryo area and sulfuric acid at a dose of 120 ml/L (P4A3). The main effect of cutting scarification treatment significantly affected all observation parameters. The best treatment was cutting scarification in the embryo area (P4). The main effect of sulfuric acid concentration significantly affected all parameters. The best treatment was sulfuric acid at a dose of 120 ml/L (A3).